Big T's and small T's: an explorative study on trauma narratives in South Africa - Naidoo, Rinisa (Rhodes University, Faculty of Humanities, Department of Anthropology)
The 21st century has seen a dramatic increase in chronic non-infectious diseases, especially in the area of mental health. Medical anthropologists have seen a rise in the development of mental illnesses in both developed and developing nations. There is, however, little research conducted on trauma narratives that do not stem from political violence from an anthropological lens. South Africa has various understandings of trauma depending on the cultural context and it is crucial to examine these narratives as this provides vital information of the daily lived experiences of trauma survivors. Key themes draw on issues of trauma denialism, communicating distress, traumatic symptoms and the development of mental illnesses as a result of traumatic exposure. The data was analysed through Goffman's (1959) Presentation of Self in Everyday Life illustrating various ways how survivors present themselves depending on the particular audience. This research employed both qualitative and quantitative research methods to gather a holistic understanding of trauma survivors. With the use of semi-structured interviews of Stressful Life Events Questionnaire coupled with observations of online support groups for trauma survivors, this research has provided rich ethnographic evidence of the impact that culture has on trauma narratives illustrating a clear normalcy of trauma present in South Africa.
Keywords: Psychic trauma; Anthropology; Mental health -- South Africa; Apartheid -- South Africa Personal narratives; Culture Psychological aspects